QUALITY CONCIERGE SERVICES AT THE HOTEL DOUBLE TREEBY HILTON JAKARTA – DIPONEGORO - Hermawan, Malik; Kesa, Deni Daniel (Journal of Indonesian Tourism and Policy Studies, 2019)
The focus of this study is to discuss about the service quality of concierge at DoubleTree By Hilton Jakarta - Diponegoro on running the operational activities and giving the excellent service to the guest related to five dimensions of service quality. This research is descriptive research. The data were collected by means of questionnaire distribution to 30 hotel guest. The researcher suggests that the amount of concierge equipment availability to assisting operational activities must be added more and the concerness of team member concierge to every guest must be improved not only to create engagement but also to give special attention to the guest so they feel cared for during their stay in the hotel.